Appeal Admissibility: Common Features between Roman Law and Latin American Justice System - Liva, Stefano (2017)
Thanks to Severan jurists’ testimonies collected in the Digest, we know that the appeal eligibility was conditioned by the «a quo» judge’s analysis of the respect of the prescribed terms and formalities and the nature of the contested measure. Against the possible refusal of the first instance judge, the parties were given the opportunity to take their case to the «ad quem» judge, who could confirm the decision and give way to the implementation of the judgment, or accept the part’s motion and proceed to the examination of the merits of the case. The Draft of the Model Civil Procedure Code for Ibero-America (texto del anteproyecto del Código Procesal Civil Modelo para Iberoamérica) follows, on the subject of appeal, Roman discipline faithfully, as regards both the «a quo» judge’s role and the possibility of contesting the latter’s decision before the «ad quem» judge through the complaint (recurso de queja). The strong Roman stamp also arises, similarly, in Peru’s Civil Procedure Code, where the right to a second court has a very incisive constitutional backing. The traditional problem to keep the justice process within reasonable time limits is closely connected with the appeal eligibility. The solution adopted by Roman Law —to take financial penalties to discourage daring appeals, filtering thus the merely delaying appeals— could represent an interesting indication for legislators, who are still grappling with the need to ensure the right, on the one hand, to appeal and to efficiency regarding the administration of justice on the other hand.